1983
DOI: 10.1111/j.1471-4159.1983.tb09041.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Subcellular Fractions Which Are Involved in Myelin Assembly: Labeling of Myelin Proteins by a Double Radioisotope Approach Indicates Developmental Relationships

Abstract: The question of developmental relationships amongst myelin-related membranes in subfractions of myelinating mouse brain (15 days) was investigated by a time-staggered double isotope protocol using [3H]leucine and [14C]leucine. Preliminary results are interpreted and discussed in the context of a mathematical conceptualization of pulse-labeling kinetic analyses of myelin proteins in subcellular membrane compartments. Differences in ratio of the two leucine labels among proteins of myelin-containing subfractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…For example, ing similarities, are nevertheless distinct. Our findings there is evidence that MBP is synthesized close to the have confirmed previous observations obtained from immyelin compartment (Benjamins et al, 1976; Colman et munocytochemical studies; they have shed new light on al., 1982; Pereyra et al, 1983). This accords with the the relationship between the plasma membrane and finding that B3.f OLG synthesize little MBP (Yim et al, myelin; and they have also sharpened old controversies 1986) just as mature oligodendrocytes in situ do not or opened new ones.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, ing similarities, are nevertheless distinct. Our findings there is evidence that MBP is synthesized close to the have confirmed previous observations obtained from immyelin compartment (Benjamins et al, 1976; Colman et munocytochemical studies; they have shed new light on al., 1982; Pereyra et al, 1983). This accords with the the relationship between the plasma membrane and finding that B3.f OLG synthesize little MBP (Yim et al, myelin; and they have also sharpened old controversies 1986) just as mature oligodendrocytes in situ do not or opened new ones.…”
Section: Discussionsupporting
confidence: 81%
“…We believe that the availability of synthesize MBP (Sternberger, 1984). a highly purified fraction of oligodendrocyte plasma Studies with precursors have revealed that it takes 20 membrane should be instrumental in opening up new min (Pereyra et al, 1983) to 30 min (Benjamins et al, avenues of research on the plasma membrane itself and 1976; Benjamins, 1984;Colman et al, 1982) for PLP to on its transformation into myelin. get into myelin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, specific radioactivity data from the fluorography scans can safely be referred to the corresponding proteins on the Western blots. 3H-leucine deposited intracranially has been dernonstrated to be nearly equivalent with a pulse label, with an average duration of less than 5 min and with no significant reutilization of the label Pereyra et al, 1983;Smith, 1968Smith, , 1972Wiggins and Morell, 1983). Therefore, this isotope and route of administration were used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Following a relatively short transit time between their site of synthesis and site of deposition. MBPs accumulate in the myelin compartment [7]. In the CNS, maturation of a myelin sheath involves ensheathment of an axon by an oligodendroglial process followed by the formation of numerous lamellae arranged spirally around the axon.…”
Section: Introductionmentioning
confidence: 99%